Analyzing the measurement of employee performance with human resources scorecard and AHP - Happy Wanda Aisyah; Didi Samanhudi (Manajemen dan Bisnis, 2023)
The Present development of globalization is improving and having an impact on the higher rate of business competition. An Employee is one of the biggest factors for the company development, therefore it is important to assess the employee performance for the company's success. This research aims to analyze the measurement result of the employee performance using the human resource scorecard and analytic hierarchy process. The data was obtained through a questionnaire that was distributed to 25 employees in heavy equipment rental department on PT. Surya Trias Gemilang Surabaya, conducted a data adequacy test, consistency test on the questionnaire, and continued with the AHP weighting. The result showed that the company experienced a decrease in employee performance from a financial perspective which means the company needs special attention from a financial perspective. The company needs to discover the utilization of net income obtained by the company to increase effectiveness for using company assets.